If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.8(3x + 4) = 0.3 + -1(x + -3) Reorder the terms: 0.8(4 + 3x) = 0.3 + -1(x + -3) (4 * 0.8 + 3x * 0.8) = 0.3 + -1(x + -3) (3.2 + 2.4x) = 0.3 + -1(x + -3) Reorder the terms: 3.2 + 2.4x = 0.3 + -1(-3 + x) 3.2 + 2.4x = 0.3 + (-3 * -1 + x * -1) 3.2 + 2.4x = 0.3 + (3 + -1x) Combine like terms: 0.3 + 3 = 3.3 3.2 + 2.4x = 3.3 + -1x Solving 3.2 + 2.4x = 3.3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3.2 + 2.4x + x = 3.3 + -1x + x Combine like terms: 2.4x + x = 3.4x 3.2 + 3.4x = 3.3 + -1x + x Combine like terms: -1x + x = 0 3.2 + 3.4x = 3.3 + 0 3.2 + 3.4x = 3.3 Add '-3.2' to each side of the equation. 3.2 + -3.2 + 3.4x = 3.3 + -3.2 Combine like terms: 3.2 + -3.2 = 0.0 0.0 + 3.4x = 3.3 + -3.2 3.4x = 3.3 + -3.2 Combine like terms: 3.3 + -3.2 = 0.1 3.4x = 0.1 Divide each side by '3.4'. x = 0.02941176471 Simplifying x = 0.02941176471
| y=10x^2+3x-2 | | 1-s=6-6-6s | | -13+4=m-10 | | -3x+7y=2 | | 2x-12=6+4x | | -36+6= | | -5+8+(-9)= | | 3t-6=4(t+4) | | 0.7(2x+8)=2.7-(x-3) | | 54p^2-5q= | | 4c-11=4c+21 | | 81=25x | | 8+x=0 | | 24-43=3(x-1)-7 | | u+8=-6 | | 44-2=n+8 | | 8+x*2=0 | | -5y-2=1-4y | | -3(6n-8)=-36-8n | | 3(x-5)=2x-15 | | 5(15n+5)=8n-9 | | 7y-8=11y+16 | | x-9=-5+4 | | 6x^2+4x=2 | | 4(6x+8)=7-x | | 8b-4=1+7b | | 4x^2+49x+16=0 | | -8-4=4x+8-3x | | 2x=5+5 | | -8-4=4x+8-3 | | 8v-1-2+15=4v-3+v | | 8v-1-2+15=4v-3+ |